Early 16th century mercantile structures in Northern Africa: the portuguese city of Safim - Correia, Jorge (2007)
In 1415 Portugal initiated its Overseas Expansion. The conquest of Ceuta began a settling process that comprised several towns in Northern Africa which would last until 1769. Late 15th century brought three suzerainties in the southern stretch of Moroccan coastline to the Portuguese crown in exchange for the establishment of a factory in those Muslim towns. Soon, the increasing commercial advantages lead to the conquest of Azamor (Azemmour) and Safim (Safi) by Manuel I. These early 16th century conquests undertook an occupational praxis over pre-existent Islamic fabrics and implied a re-evaluation of the mercantile structures. New buildings were erected to respond to this developing market of exchanges between Portugal, the Northern African reigns and the Sahara caravans. First of all, it is important to determine graphically the exact localisation of the custom house, the exchequer or the mint, either through coeval iconography engraved by Braun or local letters to the crown. However, for Safim, it is possible to extend the study. New evidence based on a recently discovered sketch suggests a complete display of all three structures around a patio in a two store construction close to the main street and the Sea Gate. This paper attempts the reconstitution of the building, relying on both written and visual data, thus throwing some light on the architectural aspect of these central spaces of the Portuguese Expansion in North Africa. Moreover, it helps to stand out the beginning of the 16th century as the most important period of urban and military activity. Since all the physical traces of the mercantile headquarters have been erased from former Portuguese possessions waterfronts in this territory, the rescue of Safim custom house complex allows us to picture a possible model applied since Ceuta.